Frederick William Ashley papers - Ashley, Frederick William, 1863-1942.
Diary and scrapbook containing handwritten entries, chronologies, clippings, obituaries, and memorabilia relating to Ashley's career at the Library of Congress and to his personal life.
Assistant Librarian of Congress and chief of the Library of Congress Order Division.
Collection material in English.
Forms part of: Library of Congress Archives.
Keywords: Library of Congress; Library of Congress -- Officials and employees; Librarians